Educational Tour of The Bamboo Village of Telagah With Ecological Architecture - Kurnia Ardiansyah; Dwira Nirfalini Aulia (Talenta Publisher, 2023)
Bamboo is a plant that has many benefits. Bamboo is also easy to grow and cultivate and has flexible properties so bamboo plants are often used in curved structures. In the community, bamboo is usually only used as a tool in agriculture, and the processing of bamboo materials is also not studied very well. The author aspires to develop a tourism destination that educates visitors about bamboo plants as a result. The tourist destination in issue is a bamboo plant educational tourism destination where every activity is entwined with or associated with bamboo plants. As an illustration, consider the introduction of bamboo plants, bamboo farming, or bamboo crafts. There is also a resort in the region that serves as a temporary house and is constructed from bamboo plants. The author's chosen topic, which is ecological architecture, is reflected in the usage of bamboo in the home as a structure and construction material. The term